A Smart Way of Synthesis and Characterization of New DNA Based Hybrid Catalysts - Rafique, Muhammad M. A. (Current Smart Materials (Discontinued), 2018)
Background: Enzyme catalysis has always attracted the attention of researchers due to their unique characteristics and advantages. However, they suffer from disadvantages of being poor in yield, inoperative and ineffective in aqueous media and suffer from degradation at elevated temperature. These disadvantages have recently been overcome in new class of catalysts which utilize same enzyme catalyst power with metal ligand attached to double helical scaffold of DNA. The process is unique that it can be carried out in aqueous media at room temperature for a range of organic reactions. In addition to that, process is scalable and has good reproducibility. Methods: 3+2 Cycloaddition reaction is carried out in water at room temperature using a carefully selected amount of DNA as catalyst. Reaction is carried out in three schemes. In first scheme, neutral Platinum Sulfoxide complexes were prepared which are subsequently mixed with 2,2´-bipyrimidine to form Pt(bipym)Cl2 with 68.8% yield. This is mixed with Cu(II)trifloromethanesulfonate and (E) - methyl 2 - (benzylideneamino)acetate in a certain sequence to accomplish the reactions. Whole process takes 6 days with overall yield of 76%. Results: Completion of reaction as manifested by physical change of color and appearance of peaks in NMR spectra mark towards effectivity of catalyst. Appearance of peaks occurring at 8, 9.4 and 9.7 ppm showed the presence of CH node resulting from 2 - pyrimidine and 1benzene in one spectrum while peaks at 7.52, 7.83 and 8.44 ppm show the presence of CH node resulting from benzylidenimin in second spectra. Further, peaks at 3.68 ppm show the presence of CH3 node resulting from methyl group and peaks at 4.51 ppm show the presence of CH2 node resulting from methylene group. Conclusion: This study effectively shows the completion of a difficult to carry 3+2 cycloaddition reaction in water at room temperature owing to the presence of new class of hybrid catalysts which combine the power of enzyme catalysts represented by DNA with transition metal ligand attached to double helix scaffold of DNA to create a synergic effect of enhancement of their effectivity. The study provided a foot print of their effectivity for new series of reactions.
Keywords: NMR